Contribution of cork oak plantations installed after 1990 in Portugal to the Kyoto commitments and to the landowners economy - Coelho, Marta Baptista; Paulo, Joana Amaral; Palma, João Henrique Nunes; Tomé, Margarida (Forest Policy and Economics, 2012)
Cork oak stands are a part of the agroforestry ecosystem in Portugal, characterized by a low crown cover from cork oak trees, managed towards cork production, and sometimes in combination with grazing. In recent years, European Union policies gave impetus to a large area of new cork oak plantations, which have been established mainly for cork production purposes, and consequently with higher stand density than traditional agroforestry systems. These plantations are important not only for cork production but also for the carbon sequestered by these slow growing forests that won't be harvested for wood production. Thinning operations will be needed to avoid excessive inter-tree competition and wood extracted from these thinning may also provide income for the owners. In the present study, carbon sequestered and wood volumes resulting from thinning were estimated for the next 70 years. Three scenarios of different annual afforestation rates and different site indexes were tested. The resulting values for the considered scenarios show that, if the plantation rates are maintained, new cork oak plantations will have an important contribution to the Portuguese commitments to providing CO2 offsets under the Kyoto protocol. Additionally, due to the increasing values of initial density in new cork plantations, cork oak forests will produce a signiﬁcant volume of wood that may become an important contribution to the landowners' income.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon Sequestration; Cork oak; Kyoto protocol; New plantations area; Wood